1994
DOI: 10.1159/000282636
|View full text |Cite
|
Sign up to set email alerts
|

Renal Tissue Endothelin in Long-Term Complete Ureteric Obstruction in the Young Rat

Abstract: Complete obstruction of one ureter was created in 3-week-old weanling rats. The endothelin concentration in the renal tissue was measured by radioimmunoassay. In the obstructed kidney, a substantial increase was observed, after 1 week +90%, after 2 weeks +55%, and after 4 weeks + 145% compared to the control rat kidneys. The endothelin-l/endothelin-3 ratio was found to be considerably raised, indicating a predominance of the vasoconstrictor effects of the – with reference to vasoactivity – bi-potential endothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…In progressive obstructive nephropathy, renal tubules dilate and tubular epithelial cells 44 The Journal of Clinical Investigation | January 1999 | Volume 103 | Number 1…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In progressive obstructive nephropathy, renal tubules dilate and tubular epithelial cells 44 The Journal of Clinical Investigation | January 1999 | Volume 103 | Number 1…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, all Agt genotypes were normotensive after UUO in the present study. The maintenance of normotension by UUO in the zero-copy mice may relate to the production of other vasoconstrictors, such as endothelin, which are generated by the hydronephrotic kidney (44).…”
Section: Figurementioning
confidence: 99%
“…Endothelin‐1. Endothelin‐1 (ET‐1) is a potent vasoconstrictor that has been implicated in the tissue damage and dysfunction associated with UUO (Josephson & Hemsen 1994; Feldman et al. 2000) and UPJ obstruction (Taha et al.…”
mentioning
confidence: 99%
“…[29] ET-1 has been implicated in the tissue damage and dysfunction associated with UUO. [30] Kelleher et al [31] demonstrated that ET-1 has a predominant role in the development of preglomerular arteriolar stenosis in the obstructed upper urinary tract. Additionally, results have suggested that ET-1 may play a role in the progression of interstitial fibrosis after ureteral ligation.…”
Section: Resultsmentioning
confidence: 99%